2021
DOI: 10.1177/16878140211040717
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization analysis of carbon nanotubes and graphene electrode modified carbon nanotubes reinforced IPMC

Abstract: IPMC is a new type of polymer material that will act violently to the stimulation of electrical signals. IPMC has changed the traditional mechanical driving mode. However, the development of IPMC is limited by factors like manufacture cost. In order to reduce the manufacture cost of IPMC, improve the output displacement and output force of IPMC, and make IPMC closer to real life, in this paper, we use carbon nanotubes to modify the ion exchange membrane of IPMC, and PDDA to modify carbon nanotubes and graphene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…This study demonstrated that reducing surface electrode resistance could enhance the drive capability of the IPMC actuator. Moreover, Zhao Jintao et al 85,86 coated graphite and carbon nanotube electrodes onto platinum-plated IPMCs, leading to a maximum output tip displacement of 4.9 mm and a maximum output force of 39 mN. These values exceeded those of a typical Pt-electrode-based IPMC (3.18 mm and 31 mN), which verified that using this approach, not only was cost reduced, but also both maximum tip displacement and output force were increased.…”
Section: Influence Of Macroscopic Featuresmentioning
confidence: 77%
“…This study demonstrated that reducing surface electrode resistance could enhance the drive capability of the IPMC actuator. Moreover, Zhao Jintao et al 85,86 coated graphite and carbon nanotube electrodes onto platinum-plated IPMCs, leading to a maximum output tip displacement of 4.9 mm and a maximum output force of 39 mN. These values exceeded those of a typical Pt-electrode-based IPMC (3.18 mm and 31 mN), which verified that using this approach, not only was cost reduced, but also both maximum tip displacement and output force were increased.…”
Section: Influence Of Macroscopic Featuresmentioning
confidence: 77%